Author’s inner Conflict in the Songs “Love of My Life” and “Bohemian Rhapsody” - Winahyu, Sri Kusuma (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Human life at one stage may not be as perfect as the other stages, Likewise, the life of Freddie Mercury, a legendary musician who is part of the Queen music band whose songs have been worldwide since the 1970’s and are still widely known today, may experience the same. This research discusses Freddie Mercury's inner conflict through two of his songs, namely "Love of My Life" and "Bohemian Rhapsody". Theory of genetic structuralism with an approach from the author's side, supported by gay theory and psychoanalytic theory (id, ego, and superego), is used as an analytical tool in this study. The results show that Freddie Mercury was a helpless figure in dealing with the pain of the fact that he was gay. However, he showed that, whatever problems in his life, he kept walking and provided his best for the people he loved, including his fans throughout the world. He never justified his way of life, but he did not want to blame anyone, except his own inner conflict.